2007
DOI: 10.1016/j.spinee.2006.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Response of lumbar paraspinal muscles spindles is greater to spinal manipulative loading compared with slower loading under length control

Abstract: The results indicate that the duration and amplitude of a spinal manipulation elicit a pattern of discharge from paraspinal muscle spindles different from slower mechanical inputs. Clinically, these parameters may be important determinants of an HVLA-SM's therapeutic benefit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
53
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(60 citation statements)
references
References 44 publications
5
53
0
2
Order By: Relevance
“…This is supported by observations that spinal manipulation is associated with changes in both central and peripheral nervous system activity (Dishman & Burke, 2003;Dishman, Greco, & Burke, 2008;Haavik-Taylor & Murphy, 2007b. It has been hypothesised that these changes are the product of reduced nociceptive activity and a synchronous barrage of afferent input produced by direct activation of peripheral receptors within the paraspinal structures (Maigne & Vautravers, 2003;Pickar, 2002;Pickar & 40 Bolton, 2012;Pickar, Sung, Kang, & Ge, 2007;Triano, 2001). Concurrent measurements of improved proprioceptive performance and decreased pain levels lends support to this theory …”
Section: Integration and Motor Functionmentioning
confidence: 83%
See 1 more Smart Citation
“…This is supported by observations that spinal manipulation is associated with changes in both central and peripheral nervous system activity (Dishman & Burke, 2003;Dishman, Greco, & Burke, 2008;Haavik-Taylor & Murphy, 2007b. It has been hypothesised that these changes are the product of reduced nociceptive activity and a synchronous barrage of afferent input produced by direct activation of peripheral receptors within the paraspinal structures (Maigne & Vautravers, 2003;Pickar, 2002;Pickar & 40 Bolton, 2012;Pickar, Sung, Kang, & Ge, 2007;Triano, 2001). Concurrent measurements of improved proprioceptive performance and decreased pain levels lends support to this theory …”
Section: Integration and Motor Functionmentioning
confidence: 83%
“…These findings suggest that spinal manipulation results in a 45 relatively synchronous, high frequency, barrage of sensory input from the activation of these receptors, as well as the physical event of the movement itself. This would all occur over the very brief (<150 ms) duration of the manipulative thrust (Pickar, 2002;Pickar et al, 2007).…”
Section: Activation Of Peripheral Receptorsmentioning
confidence: 99%
“…However, a number of chiropractic practitioners, educators, and researchers challenge this fundamental assumption (Huijbregts, 2007;Keating et al, 2005). Pickar et al have demonstrated SM loading effects in cats without targeting a predetermined mechanical derangement (Pickar et al, 2007;Pickar and Kang, 2006). Chiradejnant et al examined whether clinician-selected mobilization techniques were more effective in relieving low back pain than randomly-selected mobilization techniques (Chiradejnant et al, 2003).…”
Section: Subluxation As An Indicator For Spinal Manipulationmentioning
confidence: 99%
“…Although most commonly associated with the chiropractic profession, an increasing number of allied health care providers such as physicians, physiotherapists, osteopaths and orthopedic specialists are also incorporating SMT into their practices (Symons et al, 2002;Tsung et al, 2005;Pickar et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…force) or the body's response to such an input (eg. vertebral displacement) Kirstukas & Backman, 1999;Keller et al, 2006b;Keller et al, 2006a;Colloca et al, 2006;Triano, 2001;Solinger, 2000;Keller & Colloca, 2002;Sung et al, 2005;Dishman et al, 2005;Pickar & Kang, 2006;Pickar et al, 2007;). …”
Section: Introductionmentioning
confidence: 99%